A contemporary review of snoRNAs in cardiovascular health: RNA modification and beyond - Noah Peter Jagielski; Amit Kumar Rai; K. Shanmugha Rajan; Vatsal Mangal; Venkata Naga Srikanth Garikipati (Elsevier, 2024)
As cardiovascular diseases continue to be the leading cause of death worldwide, groundbreaking research is being conducted to mitigate their effects. This review looks into the potential of small nucleolar RNAs (snoRNAs) and the opportunity to use these molecular agents as therapeutic biomarkers for cardiovascular issues specific to the heart. Through an investigation of snoRNA biogenesis, functionality, and roles in cardiovascular diseases, this review relates our past and present knowledge of snoRNAs to the current scientific literature. Considering the initial discovery of snoRNAs and the studies thereafter analyzing the roles of snoRNAs in disease, we look forward to uncovering many other noncanonical functions that could lead researchers closer to finding preventive and curative solutions for cardiovascular diseases.